INVESTIGATION BY EXPERIMENT OF HYBRID EPOXY COMPOSITES CONTAINING COCONUT FIBRE, BAMBOO FIBRE, AND PLASTIC PARTICULATES (International Journal of Food and Nutritional Sciences, 2021)
Plastic is one of the most widely used materials in the world at this time; nonetheless, its production and disposal are major contributors to environmental degradation and the depletion of landfill space. The recovery of the material from old plastic via recycling allows for its subsequent use in the production of new plastic goods such as containers, plastic lumber, and particle boards. Before this can take place, the waste plastic will first be shredded into little pieces, preparing it for further processing and making it suitable for shipment. The enormous numbers of these various types of plastic that are now being sold will, in the end, end up in landfills or other types of garbage dumps. Because of this, difficulties are being caused by waste products owing to the large quantity of garbage that is created, the fact that it is not biodegradable, and the fact that its short life cycle results in the quickest depletion of natural resources. As a result, the amount of waste generated and the amount of material used in its creation have both grown.We are developing this research into a model for the recycling of plastic garbage in home areas, industrial areas, and other areas. Plastic waste is present in enormous quantities in this particular location. Plastic recycling, also known as reprocessing, is the process of collecting, sorting, processing, and reusing discarded plastic materials that would otherwise be disposed of as solid waste. If these materials were not recycled, they would become landfill debris. Used plastic bottles may be reduced to smaller particle sizes using a machine called a waste plastic shredder. This improves the bottle's portability, ease of use, and readiness for incorporation into another new product. With the assistance of a plastic shedding machine, we are able to reach the conclusion that plastic is shredded; as a result, we also develop and produce plastic shredder machines.Shredders for plastic, hybrid composites, epoxy, and mechanical properties are some of the key phrases here.